(untitled) (Stavební obzor - Civil Engineering Journal, 2017)
Traffic flow is a complex phenomenon that needs better understanding of basic concepts and methods for its analysis. As a solution to practical problems, computer simulation has been proved to be a powerful tool in replicating complex traffic systems which allows experimentation to the basic traffic flow system. Various methods are available in literature, some of the methods use statistical tools to verify the difference between simulated and actual outputs and some are based on optimization which tries to minimize the error. For the present work, suitable methodology is adopted for the calibration process. Field data is collected, statistical tests are performed. For the simulation, VISSIM microscopic simulation tool is used and data analysis is performed by considering individual parameters and performance measures like speed, volume and random seed number. Statistical tests have been performed to check the sensitivity of the different simulation parameters. Calibration is done using trial and error method and optimization is performed using solver function. The maximum simulated flow rate was found with default values as 4599 veh/hr, and with calibrated values is 5147 veh/hr which is close to the target capacity 4958 veh/hr as obtained using field composition. Calibrated values of CC0 and CC1 and CC2 parameters were found as most optimized values to achieve target capacity. Finally, validation of calibrated parameter was performed by using different section of a multilane highway.